Seeking meaning, seeking justice in a post-Cold War world - Keene, Judith; Rechniewski, Elizabeth (New perspectives on the Cold War ;, 2018)
Seeking Meaning, Seeking Justice in the Post-Cold War World, edited by Judith Keene and Elizabeth Rechniewski, addresses the diverse modes by which the Cold War is being re-assessed, with major focus on countries on the periphery of Cold War confrontation.